Geschlecht und Soziale Arbeit - Thiessen, Barbara; Brückner, Margrit; Köttig, Michaela; Rose, Lotte; Rubin, Yvonne (Nomos Verlagsgesellschaft mbH & Co. KG, 2026)
Gender is an essential category in social work that is also effective when professionals do not recognise or reflect on it. It is not only clients who are subject to gender patterns; structures and concepts are also influenced by gender relations. The book therefore takes up examples of central topics in social work and reflects on them from a critical gender perspective. These include gender diversity, family, love, violence, space and right-wing extremism. The book is aimed at students, professionals and teaching staff, and aims to encourage gender-critical, academic thinking and make current controversies transparent.